Factors Associated with the Incidence of Dysmenorrhea in Young Women at Ibnu Taimiyah Vocational School 2020 - Novita Lusiana (Institute Of Computer Science (IOCS), 2021)
The incidence of primary dysmenorrhea can affect the quality of life, productivity and utilization of health services during the reproductive period of women. The incidence of primary dysmenorrhea also interferes with the daily activities of some adolescents because of the pain they feel (Sakinah, 2016). Cramps due to strong menstruation can cause endometriosis (growth of uterine tissue outside the uterus that causes pain), complaints of dysmenorrhea should always be taken seriously and efforts must be made to reduce its incidence (Corwin, 2009). One of the government's efforts to address adolescent problems is the establishment of the Youth Care Health Service Program (PKPR) (Depkes, 2009). As for the variables which are risk factors for menarche, exercise habits, menstrual length and family history.